Implikasi Penetapan Darurat Masa Covid-19 Sebagai Keadaan Force Majeure Pada Perjanjian Sektor Pariwisata - Yogahastama, Riesta; Fajar, Moh. Ibnu (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to determine the implications of force majeure due to the Covid-19 pandemic on tourism sector agreements. This study used a sociological juridical approach. This research emphasized secondary sources of material, both field data, conditions in the field, and the form of regulations and legal theories. The results showed that the impact during the pandemic and the new normal was very significant. The factor that caused force majeure to take effect in the tourism sector in the Madura island region at the time of the Covid-19 epidemic was an excuse for not being able to fulfill obligations due to the disappearance of objects or destinations that are the subject of the agreement. The impact was arising from the imposition of force majeure on the tourism sector agreement in the Madura region during the Covid-19 pandemic, the tourism sector business actors canceled the agreement unilaterally by causing losses to the tourism sector business actors.